Microwave-Treated Physically Cross-Linked Sodium Alginate and Sodium Carboxymethyl Cellulose Blend Polymer Film for Open Incision Wound Healing in Diabetic Animals-A Novel Perspective for Skin Tissue Regeneration Application - Saima Mahmood; Nauman Rahim Khan; Ghulam Razaque; Shefaat Ullah Shah; Memuna Ghafoor Shahid; Hassan A. Albarqi; Abdulsalam A. Alqahtani; Ali Alasiri; Hafiz Muhammad Basit (MDPI AG, 2023)
This study aimed at developing the microwave-treated, physically cross-linked polymer blend film, optimizing the microwave treatment time, and testing for physicochemical attributes and wound healing potential in diabetic animals. Microwave-treated and untreated films were prepared by the solution casting method and characterized for various attributes required by a wound healing platform. The optimized formulation was tested for skin regeneration potential in the diabetes-induced open-incision animal model. The results indicated that the optimized polymer film formulation (MB-3) has significantly enhanced physicochemical properties such as high moisture adsorption (154.6 ± 4.23%), decreased the water vapor transmission rate (WVTR) value of (53.0 ± 2.8 g/m2/h) and water vapor permeability (WVP) value (1.74 ± 0.08 g mm/h/m2), delayed erosion (18.69 ± 4.74%), high water uptake, smooth and homogenous surface morphology, higher tensile strength (56.84 ± 1.19 MPa), and increased glass transition temperature and enthalpy (through polymer hydrophilic functional groups depicting efficient cross-linking). The in vivo data on day 16 of post-wounding indicated that the wound healing occurred faster with significantly increased percent re-epithelialization and enhanced collagen deposition with optimized MB-3 film application compared with the untreated group. The study concluded that the microwave-treated polymer blend films have sufficiently enhanced physical properties, making them an effective candidate for ameliorating the diabetic wound healing process and hastening skin tissue regeneration.